Interaction of Trypanosoma cruzi Gp82 With Host Cell LAMP2 Induces Protein Kinase C Activation and Promotes Invasion - Onofre, Thiago Souza; Rodrigues, João Paulo Ferreira; Shio, Marina Tiemi; Macedo, Silene; Juliano, Maria Aparecida; Yoshida, Nobuko (Frontiers in Cellular and Infection Microbiology, 2021)
The surface molecule gp82 of metacyclic trypomastigote (MT) forms of Trypanosoma cruzi, the protozoan parasite that causes Chagas disease, mediates the host cell invasion, a process critical for the establishment of infection. Gp82 is known to bind to the target cell in a receptor-dependent manner, triggering Ca2+ signal, actin cytoskeleton rearrangement and lysosome spreading. The host cell receptor for gp82 was recently identified as LAMP2, the major lysosome membrane-associated protein. To further clarify the mechanisms of MT invasion, we aimed in this study at identifying the LAMP2 domain that interacts with gp82 and investigated whether target cell PKC and ERK1/2, previosuly suggested to be implicated in MT invasion, are activated by gp82. Interaction of MT, or the recombinant gp82 (r-gp82), with human epithelial HeLa cells induced the activation of Ca2+-dependent PKC and ERK1/2. The LAMP2 sequence predicted to bind gp82 was mapped and the synthetic peptide based on that sequence inhibited MT invasion, impaired the binding of r-gp82 to HeLa cells, and blocked the PKC and ERK1/2 activation induced by r-gp82. Treatment of HeLa cells with specific inhibitor of focal adhesion kinase resulted in inhibition of r-gp82-induced PKC and ERK1/2 activation, as well as in alteration of the actin cytoskeleton architecture. PKC activation by r-gp82 was also impaired by treatment of HeLa cells with inhibitor of phospholipase C, which mediates the production of diacylglycerol, which activates PKC, and inositol 1,4,5-triphosphate that releases Ca2+ from intracellular stores. Taken together, our results indicate that recognition of MT gp82 by LAMP2 induces in the host cell the activation of phosholipase C, with generation of products that contribute for PKC activation and the downstream ERK1/2. This chain of events leads to the actin cytoskeleton disruption and lysosome spreading, promoting MT internalization.